Histology: A Text and Atlas: With Correlated Cell and Molecular Biology. Eighth Edition, 2018 Authors: Wojciech Pawlina; Michael H. Ross - Editorial office of journal "Morphologia" (Морфологія, 2019)
Combining a reader-friendly textbook and a rich, full-color atlas, this bestselling resource equips medical, dental, health professions, and undergraduate biology and cell biology students with a comprehensive grasp of the clinical and functional correlates of histology and a vivid understanding of the structural and functional details of cells, tissues, and organs.